2022
DOI: 10.3390/membranes13010010
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of Formation and Disordering of YBaCo2O6-δ Double Perovskite as a Base for Novel Dense Ceramic Membrane Materials

Abstract: Differential scanning calorimetry studies of the complex oxide YBaCo2O6-δ (YBC), combined with the literature data, allowed outlining the phase behavior of YBC depending on the oxygen content and temperature between 298 K and 773 K. The oxygen nonstoichiometry of single-phase tetragonal YBC was measured at different temperatures and oxygen partial pressures by both thermogravimetric and flow reactor methods. The defect structure of YBC was analyzed. As a result, the thermodynamic functions (, ) of the defect r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
19
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(23 citation statements)
references
References 38 publications
(42 reference statements)
4
19
0
Order By: Relevance
“…[145] Although YBaCo 2 O 5 + δ and HoBaCo 2 O 5 + δ are susceptible to decomposing in air at high temperatures, they have gained attention due to their lower TEC values. [146][147][148] Nevertheless, stability can be achieved through controlled and selective doping strategies. Additionally, research demonstrated that replacing ions with smaller alkali ions at the Ba 2 + site could greatly improve the electrochemical performance, leading to a significant alteration in oxygen non-stoichiometry.…”
Section: Double Perovskite Materialsmentioning
confidence: 99%
“…[145] Although YBaCo 2 O 5 + δ and HoBaCo 2 O 5 + δ are susceptible to decomposing in air at high temperatures, they have gained attention due to their lower TEC values. [146][147][148] Nevertheless, stability can be achieved through controlled and selective doping strategies. Additionally, research demonstrated that replacing ions with smaller alkali ions at the Ba 2 + site could greatly improve the electrochemical performance, leading to a significant alteration in oxygen non-stoichiometry.…”
Section: Double Perovskite Materialsmentioning
confidence: 99%
“…Over the past few years, owing to its unique crystal structure, considerable efforts have been directed towards investigating the MIEC double perovskite oxides LnBaCo 2 O 5+δ (Ln = Lanthanide). These materials find potential applications across a multitude of domains, such as magnetism [15][16][17], SOFCs, proton-conductive ceramic fuel cells [18][19][20][21][22][23][24][25], water electrolysis [26][27][28], CO 2 electrolysis [29], chemical sensors [30][31][32], ceramic semi-permeable membranes [33][34][35], metal-air batteries [36,37], soot combustion [38], supercapacitors [39], photocatalysis [40], and solar-driven thermal storage [41,42]. Given the diverse requirements in terms of physicochemical properties for each application, this article will exclusively focus on novel strategies employed in advancing double perovskites for use as cathode catalysts in SOFCs.…”
Section: Introductionmentioning
confidence: 99%
“…Oxygen nonstoichiometry was shown to affect various properties of REBaCo 2 O 6-δ , including magnetic properties [27], temperatures of phase transitions and thermodynamic properties [27,28], and electronic and oxide ion transport [29]. It is of great importance to highlight that the oxygen content of an oxide material, being measured reliably depending on temperature (T) and oxygen partial pressure (pO 2 ), enables validating its defect structure model and, consequently, evaluating the thermodynamics of defect interactions.…”
Section: Introductionmentioning
confidence: 99%
“…The Y-containing double perovskite cobaltite, YBC, was shown [28] to undergo two structural transitions upon increasing temperature: the first tetragonal (P4/mmm, 332-type superstructure) phase transforms to an orthorhombic (Pmmm and 122-type superstructure) one and then to a tetragonal phase (P4/mmm, 112-type superstructure). The former transition occurs due to the change of the ordering pattern of oxygen vacancies and the latter because of complete disordering of oxygen vacancies.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation